Prospective antimycotoxigenic action of wild Opuntia ficus-indica by-products - Ahmed Noah Badr; Karolina Gromadzka; Mohamed Gamal Shehata; Kinga Stuper-Szablewska; Kinga Drzewiecka; Adel Gabr Abdel-Razek (Czech Journal of Food Sciences, 2020)
Numerous natural compounds perform pharmaceutical, antimycotic and antitoxic purposes in the body system. The aim was to evaluate new phytoconstituents that provide antimycotoxigenic properties against mycotoxins. Bioactive materials chosen were fruit peels and cladodes of wild Opuntia ficus-indica containing a measurable quantity of bioactive phytochemicals. The highest concentration of bioactive metabolites was recorded for protocatechuic and t-cinnamic acids. A reduction effect of bioactives was estimated against aflatoxins, ochratoxin A and zearalenone in a simulated body system. Antifungal activity was determined in liquid media to evaluate antimycotic properties. Lyophilised extracts caused an aflatoxin reduction in media by 14.65% to 23.77% for fruit peels and cladodes, respectively. It caused a decrease of 59% zearalenone and 51% of ochratoxin A in a in a simulated body fluid. The cladode extract manifested better antimycotic and antimycotoxigenic characteristics due to its bioactive contents. These results support a modern antimycotoxin trend of food preservation that has a considerable impact on food safety.